Implementación de VOIP en el bloque académico de la Universidad Técnica de Cotopaxi extensión La Maná con el estándar h.323 versión 4.0 - Toapanta Sangovalin, Mayra Jaqueline (2013)
The present work of implementing VoIP at the Cotopaxi Technical University Extension La Maná, consists of the following important points: In the first chapter are analyzed some concepts and fundations related to VoIP, Risk Factors, Performance, Protocols, VoIP Codecs, the Linux – Centos platform , Asterisk, Elastix....